Pengaruh Pengalaman Kerja Dan Literasi Digital Terhadap Produktivitas Kerja Karyawan AN Sport Tasikmalaya - Lusiani Wahyu Fauziah; Askolani Askolani; Arga Sutrisna (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the effect of workÂ experience and digital literacy on employee work productivity at the Tasikmalaya AN Sport Convection The population in this research is the special sewing and cutting production department with 42 employess. The sampling technique was carried out by means of saturated sampling. The research method used is quantitative which in this analysis uses multiple linear regression equations. Data were processes using SPSS version 25. The resuts of this study indicate that work experience and digital literacy have a positive and significant effect on employee work productivity at the Tasikmalaya AN Sport Convection.